The Nexus Between Plant and Plant Microbiome: Revelation of the Networking Strategies - Babalola, Olubukola Oluranti; Fadiji, Ayomide E.; Enagbonma, Ben J.; Alori, Elizabeth T.; Ayilara, Modupe S.; Ayangbenro, Ayansina S. (Frontiers in Microbiology, 2020)
The diversity of plant-associated microbes is enormous and complex. These microbiomes are structured and form complex interconnected microbial networks that are important in plant health and ecosystem functioning. Understanding the composition of the microbiome and their core function is important in unraveling their networking strategies and their potential influence on plant performance. The network is altered by the host plant species, which in turn influence the microbial interaction dynamics and co-evolution. We discuss the plant microbiome and the complex interplay among microbes and between their host plants. We provide an overview of how plant performance is influenced by the microbiome diversity and function.